Analisis Tingkat Risiko Proyek Pelaksanaan Pemeliharaan Jalan Untuk Meningkatkan Kinerja Mutu Proyek Jalan Di Kabupaten Malang - Bowo Nyata Utama, Robertus Tri; Setyowati, Edhi Wahjuni; Harimurti, Harimurti (Rekayasa Sipil, 2017)
In every road maintenance project implementation there are always unpredictable risks affecting the quality of the project performance. This study aims to obtain the most dominant risks affecting the quality performance of road maintenance projects in Malang Regency using Analysis Hierarchy Process (AHP) method and Multiple Linear Regression. The AHP method was chosen to observe the highest level of the risk, while the Multiple Linear Regression method was selected to find risk events which have significant effect upon the quality degradation of the project. The results showed that the risk of material specification insufficiency reaches the highest risk level with risk factor value of 0.584, while the risking events caused by materials and human resources insufficiency is the most significant influences affecting the quality degradation of the project performance.